1996
DOI: 10.21273/horttech.6.3.168
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Management of Drip-irrigated Vegetables

Abstract: Drip irrigation provides an efficient method of fertilizer delivery virtually free of cultural constraints that characterize other production systems. Achieving maximum fertigation efficiency requires knowledge of crop nutrient requirements, soil nutrient supply, fertilizer injection technology, irrigation scheduling, and crop and soil monitoring techniques. If properly managed, fertigation through drip irrigation lines can reduce overall fertilizer application rates and minimize adverse environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 10 publications
(13 reference statements)
2
35
0
9
Order By: Relevance
“…As a measure to cope with drought stress, producers have been adopting more and more irrigation practices. Currently, drip fertigation is increasingly preferred since it provides both water and nutrients to match crop demand and has the potential to manage both water and nutrients in a sustainable manner (Hartz and Hochmuth, 1996). Since tomato is a N sensitive crop, relatively low cost for fertilizer N and high price for tomato fruit could prompt farmers to over fertilize processing tomato, thus possibly causing environmental problems (Rinaldi et al, 2007).…”
mentioning
confidence: 99%
“…As a measure to cope with drought stress, producers have been adopting more and more irrigation practices. Currently, drip fertigation is increasingly preferred since it provides both water and nutrients to match crop demand and has the potential to manage both water and nutrients in a sustainable manner (Hartz and Hochmuth, 1996). Since tomato is a N sensitive crop, relatively low cost for fertilizer N and high price for tomato fruit could prompt farmers to over fertilize processing tomato, thus possibly causing environmental problems (Rinaldi et al, 2007).…”
mentioning
confidence: 99%
“…Fertigation intervals of 11-22 d did not affect yield in bell pepper (Storlie et al, 1995). Generally, it has been noted that the total amount of nutrient given over a certain time period is more important than the frequency of application (Hartz and Hochmuth, 1996).…”
Section: Resultsmentioning
confidence: 94%
“…Burt et al (1995) and Hartz and Hochmuth (1996) suggested the use of the root zone soil solution [NO 3 À ] to assist in the N management of vegetable crops, also using a sufficiency value of 5 mmol NO 3 À L À1 . Burt et al (1995) and Hartz and Hochmuth (1996) suggested the use of the root zone soil solution [NO 3 À ] to assist in the N management of vegetable crops, also using a sufficiency value of 5 mmol NO 3 À L À1 .…”
Section: Nitrate Concentration Of the Soil Solution In The Root Zonementioning
confidence: 99%